Productivity improvement using VSM at TT Electronis Sdn Bhd - Muhammad Najmi, Ahmat (2016)
This project presents the application of the VSM as improvements at TT electronics Sdn Bhd. A process is the transformation of raw materials into product that custom needed. An operation is the from receiving raw material, tinning, winding, forming, header assembly, epoxy application, oven curing, cooling, cutting, pitch 1-VMI,boundary VMI, VMI, VMI mantis, testing and packaging. The objectives of this project are to study existing process of product HA00-10502LF, to eliminate waste and non-value added in the process and to improve productivity by using Value Stream Mapping. The methodology was creates by draw the current state of the VSM and generate the future state of VSM to developed the improvement action plan, the future value stream map was plotted and the improvement was highlighted at selected area that needs to improve. The simulation model of the future stream map was build using Witness software. The tool of VSM used in this project successfully achieved.